Iron-regulatory liver hormone hepcidin and its place in the system of congenital immunity - O. A. Smirnov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present literature data on iron-regulatory hormone of the liver hepcidin and mechanisms of its involvement in reactions of congenital immunity.Original positions. Hepcidin is coded by HAMP gene (Hepcidin Antimicrobial Peptide) in chromosome 19. Expression peptide mRNA in hepatocytes is induced by proinflammatory cytokines (IL-1α, IL-6 and TNF-α) similar to acute phase proteins of inflammation, and also by liver iron overload. Hepcidin promotes elevation of natural resistance of the body to infection, first of all due to direct bactericidal effect. Moreover, as key iron-regulatory hormone at conditions of infectious process it initiates systemic rearrangement of iron metabolism, reducing its availability to microorganisms. So-called inflammation anemia (anemia of chronic diseases) serves as clinical and morphological manifestation of this rearrangement, which severity correlates to unfavorable course of chronic hepatitis B and C, as well as neoplastic, renal and cardiac diseases. There are data on involvement of hepcidin in suppression of р53- controlled tumors.Conclusion. Unique properties of hepcidin allow to consider this peptide as a part, linking two major systems of homeostasis maintenance – nonspecific protection of the body and iron metabolism.